The impact of hypoxic training at different altitudes on human physiology, biochemistry, and cytogenetics - A. Demchenko, Georgiy; N. Abdreshov, Serik; U. Koibasova, Laura; A. Yessenova, Makpal; N. Yeshmukhanbet, Anar (Edelweiss Applied Science and Technology, 2024)
This study investigated the impact of dosed hypoxic normobaric exercises on the physio-biochemical parameters of blood and lymph circulation, as well as cytogenetic changes in red blood cells (RBC), using a Sprague Dawley Rat Model. Hypoxic training was conducted in an animal hypoxic chamber. The session lasted 34-35 minutes. The O2 content was 20.5% at the beginning of the session; then, it dropped to 14.8% within 4-5 minutes, corresponding to a rise to an altitude of 2,900-3,000 m, and was maintained at that level until the end of the session. The hypoxic training cycle increased the RBC count by 4.1%, the hemoglobin count by 4.2%, the blood oxygen capacity by 8.3%, the circulating blood volume by 16.7%, and interstitial metabolism and lymph circulation by 30.6%. A cytogenetic study revealed an increase in erythropoiesis-reticulocyte count by 40.3% and a slightly higher frequency of micronucleated erythrocytes. We observed economization of the heart, respiration, activation of glucose transport by 33.5%, increased lipid utilization, and increased antioxidant protection. These parameters especially changed when hypoxic training was combined with physical activity. Hypoxic training with physical activity expands the body’s compensatory and adaptive capabilities by increasing the reserves of the respiratory, cardiovascular, and lymphatic systems.